Rural Landless Women Labourers :problems and prospects - Balakrishnan A. (New Delhi Kalpaz Publication, 2005)
With special reference to Dindigul Anna District in Tamil Nadu.
Includes statistical tables.
Keywords: Rural women -- Employment; Rural women -- India -- Dindigul Anna (District); Poor women- Employment